Peningkatan Kompetensi Digital Guru SMPN 20 Dumai Melalui Pelatihan Media Pembelajaran Berbasis Canva - Sesriyani, Lodya; Said Permana, Putut; Prasetyawan, Enggar (Pekodimas : Jurnal Pengabdian Kepada Masyarakat, 2026)
This training program is designed to enhance the digital competency of teachers at SMPN 20 Dumai, specifically focusing on the integration of Canva into the teaching and learning process. This initiative is driven by the urgent need for high-quality, interactive, and visually appealing instructional media that meets the demands of modern digital education. The program will be held over three days, from October 20 to 22, 2025. Given the geographical distance, the training will be conducted virtually via Zoom. The facilitating team consists of three lecturers from the Economic Education Study Program at Universitas Pamulang, supported by two students.The training methodology follows a structured approach, combining theoretical lectures, step-by-step demonstrations, and hands-on workshops. Participants will first explore the importance of visual media in education before moving into practical sessions where they learn to use Canva’s features to create presentations, infographics, and posters. To ensure every teacher masters the material, the program includes dedicated Q&A and discussion sessions, providing personalized guidance as they complete their creative projects. Keywords: Canva, SMPN 20 Dumai, Teacher